Star Wars. The High Republic. The edge of balance : Precedent - Older, Daniel José (Star Wars: the high Republic., 2023)
"One hundred and fifty years before Starlight Beacon shone its light into the Outer Rim, the galaxy was filled with new threats and nameless unknowns. The distant planet Banchii is still unexplored when the young Wookiee Jedi Arkoff journeys to Dalna to aid his fellow Jedi in the fight against the secretive faction the Path of the Open Hand. Along with his former Master Ravna and her droid ZZ, Arkoff joins the fight at the Battle of Dalna, and during the struggle a terrifying threat emerges. Arkoff's longtime friend, Jedi Knight Azlin Rell, falls victim to an unseen force whose effect on the Jedi is unlike anything previously encountered. Will Arkoff's past come back to haunt him, or will it be the key to tilting the balance in their fight against the Nihil over a century later?"--Amazon